SITUASI SOSIAL YANG TERGAMBAR PADA PUISI-PUISI CARL SANDBURG - IZAAK, DANIEL LAURENS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study which is entitled â€œSocial Situation depicted in Carl Sandburgâ€™s Poemsâ€ focusing on the social situationÂ appeared in every single poem written by Carl Sandburg. The writer chooses ten poems which are the most famous literary works by Carl Sandburg and analyzes them by using extrinsic and intrinsic approach to discover the social meaning of every poem.This study uses the theory of Wellek and Werren (1976) about the relationship of literature and life. The purpose of this study is to identify and analyze the social situation in the ten poems written by Carl Sandburg and describe about the social situation depicted in his poems. The result of this study can be summarized as follows: all of the ten poems written by Carl Sandburg describe about the situation in Chicago and some of the poems describe about the nation. The social situationÂ depicted in Carl Sandburg poems are about poverty of the big city, the situation of the working class in big city, the spirit of people of the nation, social problems in the big city and the rights of poor people. The social situation depicted in Carl Sandburgâ€™s poems are dominated by the social problems that could not be solved by the government Â Keywords: Poems, Extrinsic Approach, Social Situation, Carl Sandburg